Knowledge and Attitude with Hypertension Prevention Behavior in Adolescents - Sugiarto, Heri; Endharti, Restu Sri; Cahyati, Widya Hari (Journal of Creativity Student, 2025)
Background: prevalence of hypertension worldwide reaches more than 1.3 billion people (31%) The prevalence of hypertension in Indonesia is 34.1%. This is an increase compared to the prevalence of hypertension in Riskesdas in 2013 of 25.8%. This study aims to determine the relationship between knowledge and attitudes with hypertension prevention behavior in adolescents. Methods: This research used type of descriptive quantitative research with a cross sectional approach. The number of samples used was 384 adolescent respondents in the Sidorejo Health Center were using nonprobability sampling technique, namely accidental sampling. The research instrument used a questionnaire to adolescent respondents and for data analysis using univariate and bivariate analysis. Results: Knowledge about hypertension prevention is still lacking, attitudes towards hypertension prevention are mostly supportive and hypertension prevention behavior is categorized as good. The results showed that there was no relationship between adolescent knowledge and hypertension prevention practices, and there was a relationship between attitudes and hypertension prevention practices in adolescents. Conclusion: There is no relationship between knowledge and hypertension prevention practices, there is a relationship between attitude and hypertension prevention practices in adolescents. Efforts are needed to improve adolescents' attitudes towards hypertension, so as to support the practice of hypertension prevention.